2017
DOI: 10.5222/gkdad.2017.008
|View full text |Cite
|
Sign up to set email alerts
|

Monitorisation of Cerebral Oxygenation in Cardiac Surgeries with and Without Cardiotomy

Abstract: ÖZ Amaç:Kardiyovasküler cerrahi sırasında near infrared spektroskopi (NIRS) GiriŞKardiyovasküler cerrahi sırasında near infrared spektroskopi (NIRS) ile serebral oksijen monitörizasyonu intraoperatif monitörler arasında kabul gören ve değeri gittikçe artan bir metotdur [1,2] . Koroner cerrahisi Araştırma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…12 In a study of 37 patients by Mecher et al patients had ∆pCO 2 values greater than 6 mmHg and cardiac output were found to be low and ∆pCO 2 was decreased after fluid resuscitation. 4,13 In the study of Bakker et al followed 64 patients with sepsis, low cardiac output of 15 patients also had high values of ∆pCO 2 . 14 Therefore, ∆pCO 2 has been shown to be strongly associated with cardiac output in those studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In a study of 37 patients by Mecher et al patients had ∆pCO 2 values greater than 6 mmHg and cardiac output were found to be low and ∆pCO 2 was decreased after fluid resuscitation. 4,13 In the study of Bakker et al followed 64 patients with sepsis, low cardiac output of 15 patients also had high values of ∆pCO 2 . 14 Therefore, ∆pCO 2 has been shown to be strongly associated with cardiac output in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…19 In Türkyılmaz and his friends' study about 40 patients who underwent elective valve operation and coronary artery bypass grafting operation using CPB; they concluded that there were no significant differences in the parameters and NIRS measurements observed at the time intervals between the groups of patients with valve and coronary surgery. 13 In the study of Işıldak et al evaluating the use of cerebral oximetry in hypoperfusion monitoring in pediatric cardiac surgery; they concluded that intraoperative monitoring of perfusion with cerebral oximetry during congenital heart surgery is a valuable indicator and they also report that right and left cerebral oximetry values have fallen in cases of tissue oxygenation was impaired (ex: hypotension, hemodilution, hypovolemia, anemia) and they determined that the values were corrected when the precautions were taken. 20 In our study, rSO 2 values decreased to 58% and 59% in 2 patients during hypothermia (T3) period.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Near infrared spectroscopy monitoring is suggested to be rather useful for patients who are at high risk for neurological complications during cardiac surgery. [15] Goldman et al [16] investigated the follow-up of some of the 1,297 patients who had undergone CABG with or without NIRS, and found the stroke rate to be lower in patients who had been followed-up with NIRS during the postoperative 18 months. They reported that cerebral rSO 2 decreased when tissue oxygenation was impaired due to hypotension, hemodilution, anemia, catheter malposition during the intraoperative period, and improved when appropriate measures were taken.…”
Section: Discussionmentioning
confidence: 99%